2006
DOI: 10.1590/s0100-72032006000200005
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da terapia estro-raloxifeno sobre o endométrio de ratas

Abstract: RESUMOObjetivo: avaliar os efeitos dos estrogênios conjugados eqüinos (Ece) e do raloxifeno (Ral), isoladamente ou associados, sobre o endométrio de ratas adultas. Métodos: foram utilizadas 56 ratas adultas, ooforectomizadas, divididas aleatoriamente em sete grupos: GCont (controle); GEce (Ece 50 μg/kg); GEce/25 (Ece 25 μg/kg); GRal/0,75 (Ral 0,75 mg/kg); GRal/0,4 (Ral 0,4 mg/kg); GEce-Ral (50/0,75) -(Ece 50 μg/kg + Ral 0,75 mg/kg) e GEce-Ral (25/0,4) -(Ece 25 μg/kg + Ral 0,4 mg/kg). As drogas foram administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(26 reference statements)
0
3
0
1
Order By: Relevance
“…The combination of raloxifene with estrogens have been described both in vitro and in vivo (16)(17)(18)(19)(20)(21)(22)(23)(24). The antagonistic effect of different SERMs (raloxifene, tamoxifen, bazedoxifene, and lasofoxifene) on estradiol-treated endometrial epithelial Ishikawa cells has been demonstrated by altered expression of different genes (HOXA10, LIF, PR, and EMX2) (16).…”
Section: ' Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of raloxifene with estrogens have been described both in vitro and in vivo (16)(17)(18)(19)(20)(21)(22)(23)(24). The antagonistic effect of different SERMs (raloxifene, tamoxifen, bazedoxifene, and lasofoxifene) on estradiol-treated endometrial epithelial Ishikawa cells has been demonstrated by altered expression of different genes (HOXA10, LIF, PR, and EMX2) (16).…”
Section: ' Discussionmentioning
confidence: 99%
“…Tissue-selective estrogen complex, which comprises the combination of estrogen with a SERM, has been explored in attempts to optimize hormone replacement therapy and reduce adverse outcomes (15), including endometrial proliferation. Combinations of various estrogen formulations and raloxifene have been described both in vitro and in vivo (16)(17)(18)(19)(20)(21)(22)(23)(24), and have yielded controversial results regarding cell proliferation patterns in the endometrium, bone, and breast tissues. The combination of CE and raloxifene could potentially minimize the undesirable effects of estrogen on the uterus and breast tissues, and allow the beneficial agonistic effects of estrogen in other estrogen target-tissues (25)(26)(27)(28)(29).…”
Section: ' Introductionmentioning
confidence: 99%
“…Researches in rats demonstrated that the treatment with this drug reduces the weight of the uterus (1,12) .…”
Section: Discussionmentioning
confidence: 99%
“…Após 21 dias, realizou-se exame colpocitológico para certificar que os animais estavam castrados (Marcondes et al, 2002). (Moraes et al, 2006).…”
Section: Falência Ovariana E Intervenções Medicamentosasunclassified